Rekonstruksi Kurikulum Manajemen Pendidikan Islam Dalam Perspektif Society 5.0 - Istianatul Imamah; Khaudli, Muh. Imam (Jurnal Keislaman, 2025)
The purpose of this research is to interpret curriculum models as the development of the Islamic Education Management curriculum in the perspective of Society 5.0. This research design uses a qualitative method with a case study approach to deeply understand the dynamics and practices of developing the Islamic Education Management curriculum at KH Mukhtar Syafaat University. The data sources in this study used primary data obtained through direct interviews with faculty deans, heads of study programs, and students and secondary data obtained from relevant articles and documents, such as curriculum reports, academic publications, and education policy documents. Data collection techniques in this study used observation, interviews, and documentation. The data analysis technique used in this study refers to the Miles and Huberman data analysis model, which includes data reduction, data presentation, and conclusion drawing. The curriculum at KH Mukhtar Syafaat University is designed flexibly and based on specialization, independent study, and international perspectives, which not only equips students with technical skills, but also empowers them to develop specialized competencies, think critically, and adapt to global challenges and evolving market needs.